A Tale of Two Groups: Elementary Students’ Varied Digital Collaborative Writing Processes and Perspectives - Shimizu, Amanda (International Electronic Journal of Elementary Education, 2026)
As digital technologies become increasingly central to modern life, ensuring equitable digital literacy is essential. While many schools expanded device access during the COVID-19 pandemic, digital equity requires meaningful opportunities for students to collaborate, create, and communicate using digital tools. This study examined how two groups of elementary students participated in digital collaborative writing (CW) in varied ways, suggesting that different participation structures can support diverse learners. One group used a single scribe, encouraging collective negotiation of a single idea, while the other used multiple scribes to develop ideas in parallel. Both groups relied on elaboration, agreement, and disagreement to move ideas forward. Students valued peers who were helpful, kind, and focused, and who contributed to the shared text. We discuss how digital CW can support diverse learners by enabling flexible participation, highlighting implications for designing inclusive writing instruction in digitally mediated elementary classrooms.